The Psychology of Counter-Terrorism. - Silke, Andrew (Cass series on political violence., 2010)
This edited book explores how psychology can be used to improve our understanding of terrorism and counterterrorism. This work firstly aims to provide balanced and objective insight into the psychology of terrorists; what their motivations are, what keeps them involved in terrorist groups, and what eventually forces most to end their active involvement in terrorism. Secondly, the contributors focus on the challenging issue of how to respond to terrorism. These chapters provide information for those concerned with short-term tactical problems (e.g. interviewing), as well as those looking towards.